TWO-COMPONENT POLYURETHANE ADHESIVE HAVING SUBSTANTIALLY TEMPERATURE-INDEPENDENT MECHANICAL PROPERTIES AND HIGH STRENGTH - BURCKHARDT URS; KELCH STEFFEN (2019)
The present invention relates to a two-component polyurethane composition comprising at least 55% by weight of polybutadiene polyols based on the total amount of all polyols having a mean molecular weight of at least 500 g/mol, and at least one latent hardener, wherein the ratio of the number of reactive groups in the latent hardener to the number of OH groups present is in the range from 0.02 to0.4. The composition has a long open time, bubble-free curing, a very low glass transition temperature, high elasticity and surprisingly high strength, which are very constant over a wide temperaturerange. Furthermore, it adheres very well to metallic and non-metallic substrates, causing barely any stress cracks on glassy thermoplastics. It is thus of excellent suitability as a structural elasticadhesive for bonds subject to stress within a broad temperature range. 本发明涉及双组分聚氨酯组合物，基于平均分子量为至少500g/mol的所有多元醇的总量，其包含至少55重量％的聚丁二烯多元醇和至少种潜伏固化剂，其中潜伏固化剂的反应性基团的数目与存在的OH-基团的数目的比例在0.02至0.4的范围内。所述组合物具有长的开放时间，无气泡的固化，极低的玻璃化转变温度，高弹性和出人意